(untitled) (Damascus University Journal of agriculture sciences, 2023)
Fungal cell wall is an alternative source of chitosan. Fungal chitin and chitosan is purer, more coherent, and contains less allergens than chitin extracted from shellfish, so it is more suitable for pharmaceutical and food applications, considering that fungal mycelium can be obtained by simple, rapid, and low cost ways regardless of geographical location or season. In this study chitosan was extracted from Rhizopus stolonifer, Aspergillus niger and Penicillium italicum by submerged fermentation in Sweet Sorghum Juice (SSJ). It was observed after growing fungi on diluted Sweet Sorghum Juice (SSJ) by submerged fermentation that Rhizopus stolonifer gave the biggest amount of chitosan (4.9% of mycelium dry weight). The liquid medium was optimized to get the biggest dry weight of this fungus. The results showed that diluting the medium SSJ to 30/70 v/v in distilled water under submerged fermentation for 6 days at 25º C degree by adding 2% of peptone into medium and 150 rpm rotation speed had given the biggest dry weight of Rhizopus stolonifer.